CONDUCTING TEACHING ACTIVITIES IN JUNIOR HIGH SCHOOL BY NOT PROVIDING AN OFFICIAL DOCUMENT OF LESSON PLAN - putu ngurah rusmawan (Fakultas Ilmu Budaya, Universitas Brawijaya, 2018)
ABSTRACT The systematic lesson plans are guiding the teachers to provide the effective teaching process. It is like a direction of what the teacher should do during conducting teaching activity. The lesson plan can convey teachers’ performance in their classes in a good way. Unfortunately, many teachers still do not have enough capability to design systematic lesson plan because the teachers get difficulties in interpreting basic competences; therefore, they make a lesson plan incorrectly. The preliminary study conducted in one private junior high school, in fact, the teacher carried out the teaching activities in that school without providing official document of lesson plan. For this reason, this study aims to discuss how the teaching activities carried out by the teacher without official document of lesson plan at junior high school in Porong to achieve the basic competence. This study was conducted in the classroom of VII-1 in a natural setting, therefore, the appropriate design was qualitative research design. The subject of the study was the English teacher. To collect data, the researcher used observation. The data gained from the observation were described and analyzed to answer the research questions. The results of the study showed that the teaching activities were carried out by the teacher without providing official document of lesson plan were poor. The expectation of the basic competence of writing descriptive text had been failed to be reached. The teacher’s opening, main, and closing activities were poorly organized there were so many weakness could be found. Keyword: Teaching Activities, Lesson Plan, junior high school